PENGELOLAAN PENANGANAN ABSENSI KARYAWAN POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA TIMUR - Kartini, Iis; Yayandi, Muhamad (JAB (Jurnal Akuntansi & Bisnis), 2021)
This research was conducted to find out the Procedure for Handling Employee Attendance at the LP3I Polytechnic Jakarta, East Jakarta Campus, the Procedure for Handling Attendance for Employees was carried out by browsing the HRIS LP3I website, logging in, filling in the absences, logging out, absent automatically recorded on the website, HRD Polytechnic LP3I Jakarta Kramat Campus sent recapitulation to HRD Polytechnic LP3I Jakarta East Jakarta Campus, HRD Polytechnic LP3I Jakarta East Jakarta Campus recapitulates for internal records, HRD signs the recapitulation and reports it to the finance division. The purpose of this study was to determine the constraints and alternative solutions in problem solving. Data collection techniques through observation, namely observing directly the object under study. As for the obstacles that occur in the Procedure for Handling Employee Attendance at the LP3I Polytechnic, East Jakarta, errors often occur on the website, require internet, and how to use the website is less effective. Solutions that are made while still not effective. Keywords: Procedure, Handling, Attendance, Employee